Wireless passive sensing application using a cavity loaded evanescent mode half mode substrate integrated waveguide resonator (2011)
In this work, an evanescent mode half mode substrate integrated waveguide (HMSIW) resonator is designed for a wireless passive sensing application at 5 GHz. The wireless pressure sensor has been implemented by placing a small Polydimethylsiloxane (PDMS) cavity, covered with a metal coated membrane, on top of the original resonator or by using a cavity ground plane. When the metal coated membrane is deformed or deflected by an external pressure, it perturbs the electric field of a complementary split ring resonator (CSRR) patterned on top of the HMSIW, producing a shift in the resonance frequency. Because it operates in a microwave frequency spectrum, it offers a high pressure-frequency sensitivity. Resonance frequency as a function of an applied pressure has been presented. Also, a broadband antenna has been integrated to perform wireless interrogation of the sensor. © 2011 IEEE.